O papel dos Centros Universitários do Estado do Paraná no desenvolvimento dos ODS estabelecidos pela ONU - Cavalheiro Neto, Afonso (2023)
This study aimed to analyze the role of the University Centers of the State of Paraná in the development of the Sustainable Development Goals (SDGs) established by the United Nations (UN). Through the education and training of students, teachers and also the integration of the principles of sustainability and the SDGs in undergraduate and graduate curricula, extension programs, continuing education courses and research activities, Higher Educations Institutions (HEIs) can contribute to the dissemination of knowledge about the SDGs. Directly related to the SDGs, sustainability is one of the relevant themes addressed in HEIs, mainly through environmental education. The processes related to sustainability in HEIs are treated in teaching, research, extension and management, in order to build a sustainable educational space. However, the insertion of sustainability in the university presupposes the need for significant and challenging changes regarding management, technical and teacher training, campus structure and curricula, which involves a movement of awareness and cooperation of the entire academic community. It is, therefore, within this line of reasoning that this study is developed, especially with regard to the "2030 Agenda for Sustainable Development", as an expression of power and public policies aimed at this end. In this context, the present study sought to answer the following question: what is the role of HEIs in the development of the 2030 agenda on commitments established at the United Nations Assembly and how do the University Centers of the State of Paraná act in the development of SDGs established by the UN? The research focused on the activities developed by the university centers of Paraná in relation to the SDGs and the contribution of these activities to the promotion of sustainable development. For this purpose, the Institutional Development Plans (IDP) of the Higher Education Institutions (HEIs) mentioned were analyzed. The study was exploratory and a questionnaire was applied to 37 managers of the University Centers of the State of Paraná, of which 26 responded. The IDPs of 30 HEIs were also analyzed. The data were treated by simple statistics, using frequency distribution. As a result, the practices and strategies that the University Centers of the State of Paraná have adopted to promote the SDGs were identified. The specific objectives proposed were met, considering that, with regard to the specific objective of "Identify in scientific production what are the objectives of development Sustainable (SDGs) established by the United Nations (UN)" was presented a broad bibliographic review about the SDGs, the role that HEIs should play, as well as about the legislation that deals with the IDP. Regarding the specific objective of "To analyze the institutional development plans of the University Centers of the State of Paraná to verify the level of institutionalization of the ODS", this study presents in detail the results obtained in the analysis of these documents. With regard to the objective of "To verify what are the practices and strategies adopted by the University Centers of the State of Paraná to promote the SDGs", the results of the managers' responses to the questionnaire applied were also carefully discussed. The results referring to the analysis of the IDPs allow us to conclude that the HEIs treat, even if not explicitly, the SDGs in their IDPs. The answers of the managers to the questionnaire present, in general, coherence with the results obtained in the analysis of the IDPs. Although they have been acting in some way in the development of the SDGs, it is necessary that the HEIs and, consequently, their managers and other actors of the academic community, seek to address, in a more explicit and direct way, the SDGs in their IDPs and in their teaching, research, extension and management activities. Only with the commitment and engagement of all will it be possible to successfully fulfill the proposals of the 2030 agenda.